Sanguinarine Improves Intestinal Health in Grass Carp Fed High-Fat Diets: Involvement of Antioxidant, Physical and Immune Barrier, and Intestinal Microbiota - Yong Shi; Yuanxiang Liu; Kai Xie; Junzhi Zhang; Ya Wang; Yi Hu; Lei Zhong (MDPI AG, 2023)
An eight-week trial was conducted to investigate the effects of sanguinarine supplementation (600 μg and 1200 μg/kg) in high-fat (crude fat: 10%) diets (HF) on the intestinal physiological function of Ctenopharyngodon idellus (initial weight 50.21 ± 0.68 g), based on a basic diet (5% crude fat, CON), which were named HFLS and HFHS, respectively. The results showed that the HF diet significantly impaired the intestinal immune and physical barrier function, and disrupted the balance of the intestinal microbiota in grass carp. Compared to the HF diet, sanguinarine supplementation significantly improved the levels of serum C4, C3, AKP, IgA, and IgM, and enhanced the intestinal antioxidant capacity (gr, CuZnsod, gpx4, cat, gsto, and nrf2 expression were significantly up-regulated). Sanguinarine significantly down-regulated the expression of claudin-15 and up-regulated the expression of claudin-b, claudin-c, occludin, and zo-1 by inhibiting MLCK signaling molecules. Additionally, sanguinarine significantly down-regulated the expression of il-6, il-1β, and tnf-α and up-regulated the expression of il-10, tgf-β2, and tgf-β1 by inhibiting NF-κB signaling molecules, thereby alleviating intestinal inflammation caused by HF diets. Furthermore, compared to the HF diet, the abundance of Fusobacterium and Cetobacterium in the HFHS diet increased significantly, while the abundance of Firmicutes and Streptococcus showed the opposite trend. In conclusion, the HF diet had a negative impact on grass carp, while sanguinarine supplementation enhanced intestinal antioxidant ability, alleviated intestinal barrier damage, and ameliorated the homeostasis of the intestinal microbiota.